THE INFLUENCE OF GOOD CORPORATE GOVERNANCE, AND QUALITY OF AUDIT AGAINST THE INTEGRITY OF THE FINANCIAL STATEMENTS - Hasanuddin Hasanuddin (International Journal of Economics Management and Social Science, 2018)
This study aimed to analyze the influence of corporate governance and quality audits that could affect the integrity of the financial statements on companies listed in the Indonesia Stock Exchange. The integrity of the financial statements is defined as the extent to which the financial statements show a true and honest information. Factors corporate governance and quality audit analyzed its impact on the integrity of the financial statements include the audit committees, independent directors, board size, institutional ownership , managerial ownership and the quality of KAP. This research was conducted with quantitative methods on the financial statements of manufacturing companies listed in Indonesia Stock Exchange during the period 2010-2013. The total sample is 24 companies determined through purposive sampling method. Results showed that not all consistent with the hypothesis and significant effect. However, audit committees, independent directors, board size, and quality of KAP shown to have a significant influence on increasing the integrity of the financial statements.